2012
DOI: 10.1007/s12035-012-8372-8
|View full text |Cite
|
Sign up to set email alerts
|

Noise-Induced Inner Hair Cell Ribbon Loss Disturbs Central Arc Mobilization: A Novel Molecular Paradigm for Understanding Tinnitus

Abstract: Increasing evidence shows that hearing loss is a risk factor for tinnitus and hyperacusis. Although both often coincide, a causal relationship between tinnitus and hyperacusis has not been shown. Currently, tinnitus and hyperacusis are assumed to be caused by elevated responsiveness in subcortical circuits. We examined both the impact of different degrees of cochlear damage and the influence of stress priming on tinnitus induction. We used (1) a behavioral animal model for tinnitus designed to minimize stress,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
197
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(208 citation statements)
references
References 94 publications
11
197
0
Order By: Relevance
“…This cytoskeletal protein is mobilized after LTP activity and has been proposed to influence postsynaptic AMPA receptor expression that is required for LTP (reviewed by Knipper et al 2013). Interestingly, A1 Arc/Arg3.1 following noise exposure was only mobilized in animals without tinnitus and was not changed in those with tinnitus Singer et al 2013). This suggested that increased cortical firing following moderate deafferentation following noise may be the result of enhanced glutamate sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…This cytoskeletal protein is mobilized after LTP activity and has been proposed to influence postsynaptic AMPA receptor expression that is required for LTP (reviewed by Knipper et al 2013). Interestingly, A1 Arc/Arg3.1 following noise exposure was only mobilized in animals without tinnitus and was not changed in those with tinnitus Singer et al 2013). This suggested that increased cortical firing following moderate deafferentation following noise may be the result of enhanced glutamate sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Following the treatment protocols of Kaltenbach et al [42], the rats were exposed for 2 h and sacrificed 10-15 d following noise exposure (acoustic trauma, AT). This exposure paradigm has been reported to induce tinnitus in more than 90% of rats (29 out of 31 rats with tinnitus; [11]). Sham-exposed animals were anesthetized and placed in the reverberating chamber, but not exposed to acoustic stimulus (i.e., the speaker remained turned off).…”
Section: Methodsmentioning
confidence: 99%
“…Ribbon synapses of IHCs (Fig. 1) were counted as previously described [11,47]. Briefly, cross sections of the cochleae containing all three cochlear turns (apical/medial, midbasal and basal) were used for immunhistochemistry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective IHC synaptic ribbons are essential for normal auditory signaling and hearing [26]. Significant losses of IHC ribbon synapses accompanied by hearing impairment can be observed in noise-induced tinnitus [27,28]. Nevertheless, the mechanisms by which ototoxicity causes damage to synaptic ribbons are still unknown.…”
Section: Introductionmentioning
confidence: 99%